1990
DOI: 10.1093/clinchem/36.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) is an independent risk factor for myocardial infarction at a young age

Abstract: We quantified lipoprotein(a) [Lp(a)] immunochemically in young (less than 46 y) male survivors of myocardial infarction and in age-matched controls recruited from participants of the Prospective Cardiovascular Münster (PROCAM) study. We further determined apolipoprotein E polymorphism and measured triglycerides, total cholesterol, high- and low-density lipoprotein cholesterol (HDL and LDL), and apolipoproteins AI, AII, and B in the serum of these subjects. Lp(a) concentrations in serum were not correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
3
2

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(84 citation statements)
references
References 0 publications
6
73
3
2
Order By: Relevance
“…Multivariate regression analysis confirmed the negative correlation between the concentrations of Lp(a) and TG (r = -0.31; P < 0.001) as well as the positive correlation with HDL-cholesterol ( Table 2). These relationships were not observed in 1237 controls from the Prospective Cardiovascular Munster (PROCAM) Study [19,20].…”
Section: Resultsmentioning
confidence: 91%
“…Multivariate regression analysis confirmed the negative correlation between the concentrations of Lp(a) and TG (r = -0.31; P < 0.001) as well as the positive correlation with HDL-cholesterol ( Table 2). These relationships were not observed in 1237 controls from the Prospective Cardiovascular Munster (PROCAM) Study [19,20].…”
Section: Resultsmentioning
confidence: 91%
“…A number of prospective studies have demonstrated an association between Lp(a) level and the risk of coronary artery disease [10,12,36,37], but not all studies have found such a relationship [38,39]. Elevated Lp(a) levels may distinguish those patients with familial hypercholesterolaemia and clinically overt coronary heart disease from those without the disease [36,40], although it may also be regarded as a part of the clinical syndrome of familial hypercholesterolaemia [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did ®nd higher levels of Lp(a) in our ANCA-positive patients. Elevated levels of Lp(a) (³300 mg L )1 ) are an independent risk factor for cardiovascular disease, especially in patients with premature atherosclerosis [24]. Higher levels of Lp(a) have been reported in patients with SLE and anti-phospholipid syndrome as well [25,26].…”
Section: Discussionmentioning
confidence: 99%